A study to establish international diagnostic reference levels for paediatric computed tomography - J. Vassileva (2018)
© The Author 2015. Published by Oxford University Press. The article reports results from the largest international dose survey in paediatric computed tomography (CT) in 32 countries and proposes international diagnostic reference levels (DRLs) in terms of computed tomography dose index (CTDIvol) and dose length product (DLP). It also assesses whether mean or median values of individual facilities should be used. A total of 6115 individual patient data were recorded among four age groups: <1 y, >1-5 y, >5-10 y and >10-15 y. CTDIw, CTDIvol and DLP from the CT console were recorded in dedicated forms together with patient data and technical parameters. Statistical analysis was performed, and international DRLs were established at rounded 75th percentile values of distribution of median values from all CT facilities. The study presents evidence in favour of using median rather than mean of patient dose indices as the representative of typical local dose in a facility, and for establishing DRLs as third quartile of median values. International DRLs were established for paediatric CT examinations for routine head, chest and abdomen in the four age groups. DRLs for CTDIvol are similar to the reference values from other published reports, with some differences for chest and abdomen CT. Higher variations were observed between DLP values, based on a survey of whole multi-phase exams. It may be noted that other studies in literature were based on single phase only. DRLs reported in this article can be used in countries without sufficient medical physics support to identify non-optimised practice. Recommendations to improve the accuracy and importance of future surveys are provided.